2008
DOI: 10.2527/jas.2007-0756
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of alternative beef production systems based on forage finishing or grain-forage diets with or without growth promotants: 2. Meat quality, fatty acid composition, and overall palatability

Abstract: Five beef cattle management regimens were evaluated for their effect on meat quality, fatty acid composition, and overall palatability of the longis-simus dorsi (LD) muscle in Angus cross steers. A 98-d growing phase was conducted using grass silage with or without supplementation of growth promotants (Revalor G and Rumensin) or soybean meal. Dietary treatments in the finishing phase were developed with or without supplementation of growth promotants based on exclusive feeding of forages with no grain suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
55
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 78 publications
10
55
2
Order By: Relevance
“…(1 as compared with 539 and 447 mg 100 g (1 reported by Faucitano et al (2008Faucitano et al ( , 2011. However, the proportion of soluble collagen was greater (15%) than values of 10 and 9% reported by Faucitano et al (2008Faucitano et al ( , 2001.…”
Section: Meat Quality Characteristicscontrasting
confidence: 50%
See 1 more Smart Citation
“…(1 as compared with 539 and 447 mg 100 g (1 reported by Faucitano et al (2008Faucitano et al ( , 2011. However, the proportion of soluble collagen was greater (15%) than values of 10 and 9% reported by Faucitano et al (2008Faucitano et al ( , 2001.…”
Section: Meat Quality Characteristicscontrasting
confidence: 50%
“…However, the proportion of soluble collagen was greater (15%) than values of 10 and 9% reported by Faucitano et al (2008Faucitano et al ( , 2001. Shear force values for LL muscles from calves born from vitamin-injected dams tended to be lower (more tender) (P 00.06) than LL muscles from calves born from unsupplemented dams ( Table 4).…”
Section: Meat Quality Characteristicscontrasting
confidence: 48%
“…In the current study, treatment did not affect any collagen measures. Calkins et al (1986) and Faucitano et al (2008) reported no implant effect on total or soluble collagen content and percent soluble collagen. Huck et al (1991) also found collagen solubility was unaffected when more aggressive implants were administered to steers.…”
Section: Growth-promoting Technologies Effectsmentioning
confidence: 99%
“…In addition, Alfaia et al (2006) found differences in LA between meat from bullocks reared in a semi-intensive system and that from bullocks produced in a conventional intensive concentrate-based system. On the other hand, Faucitano et al (2008) found that cattle fed high concentrate diets showed a significantly decreased the proportion of ALA in Longissimus dorsi muscle lipids. Lee et al (2009) studied the effects of diets with grass or red clover silage on the proportions of LA and ALA in Longissimus dorsi muscle in dairy cull cows and found that red clover silage increased the percentages of LA and ALA. Herdman et al (2010) studied the effects of two diets, one rich in LA and the other rich in ALA and found that both affected the fatty acid composition of the lipid classes in the IMF of German Simmental bulls.…”
Section: Discussionmentioning
confidence: 93%